NEOADJUVANT ENDOCRINE THERAPY FOR PATIENTS WITH ESTROGEN-RECEPTOR-POSITIVE BREAST CANCER - V. F. Semiglazov; V. V. Semiglazov; G. A. Dashyan; P. V. Krivorotko; V. G. Ivanov; E. K. Zhiltsova; R. M. Paltuev; L. M. Bershtein; T. Yu. Semiglazova; S. S. Yerechshenko; V. V. Klimenko; V. S. Apollonova; et al. (Сибирский онкологический журнал, 2018)
More than 70 % of patients with breast cancer have estrogen-receptor-positive tumors (ER+) and are considered hormone- sensitive. That is why a vast majority of patients with early operable  tumors receive adjuvant endocrine therapy. Patients with metastatic  ER+ breast cancer also receive hormone therapy as first-line  treatment. Patients with ER+/PR+ locally advanced breast cancer  including potentially operable cases (cT2N1, cT3N0M0) are still a  subject to neoadjuvant chemotherapy in most of the oncology  centers in Russia and worldwide. More than 10 years ago, several  trials evaluating the efficacy of neoadjuvant endocrine therapy were  conducted in the Petrov Research Institute of Oncology (aromatase  inhibitors vs tamoxifen, neoadjuvant endocrine therapy vs  neoadjuvant chemotherapy, etc.) The primary endpoint was the  evaluation of pathologic complete/partial response to therapy and  the frequency of breast-conserving surgeries following neoadjuvant  treatment. We now represent 10-year long-term follow-up data on  comparison of neoadjuvant chemotherapy with neoadjuvant  endocrine therapy after retrospective determination of IHC- phenotypes of 239 patients with ER+ breast cancer. The study  results show tendency to better 10-year disease-free survival in  patients with luminal-A breast cancer who received endocrine  therapy compared to neoadjuvant chemotherapy (72.8 % vs 53.9  %, respectively, p=0.062) There were no statistically significant  differences in DFS rates among patients with the luminal B breast  cancer subtype (41 % vs 40 %) The discovery of biomarkers of  potential resistance to endocrine therapy (cycline-dependant kinase  activity [cdk 4/6], estrogenreceptor mutation [ESR1], mTOR  signaling pathway activity, co-expression of the ER and HER2neu  [ER+/ HER2neu3+]) and ways to inhibit the activity of the resistance pathways (palbocyclib, everolimus, etc.) have expanded the  armamentarium of endocrine-therapy for not only metastatic and  locally-advanced but also operable cases of ER+ breast cancer.